Decomposer food web in a deciduous forest shows high share of generalist microorganisms and importance of microbial biomass recycling - López-Mondéjar, Ruben; Brabcová, Vendula; Štursová, Martina; Davidová, Anna; Jansa, Jan; Cajthaml, Tomaš; Baldrian, Petr (The ISME journal, 2018)
Forest soils represent important terrestrial carbon (C) pools where C is primarily fixed in the plant-derived biomass but it flows further through the biomass of fungi and bacteria before it is lost from the ecosystem as CO2 or immobilized in recalcitrant organic matter. Microorganisms are the main drivers of C flow in forests and play critical roles in the C balance through the decomposition of dead biomass of different origins. Here, we track the path of C that enters forest soil by following respiration, microbial biomass production, and C accumulation by individual microbial taxa in soil microcosms upon the addition of 13C-labeled biomass of plant, fungal, and bacterial origin. We demonstrate that both fungi and bacteria are involved in the assimilation and mineralization of C from the major complex sources existing in soil. Decomposer fungi are, however, better suited to utilize plant biomass compounds, whereas the ability to utilize fungal and bacterial biomass is more frequent among bacteria. Due to the ability of microorganisms to recycle microbial biomass, we suggest that the decomposer food web in forest soil displays a network structure with loops between and within individual pools. These results question the present paradigms describing food webs as hierarchical structures with unidirectional flow of C and assumptions about the dominance of fungi in the decomposition of complex organic matter.
Keywords: Biodegradation, Environmental; biomasa; Bacteria; rostliny; uhlík; Biomass; Soil; Carbon; biodegradace; Ecosystem; Forests; Plants; houby; ekosystém; půdní mikrobiologie; Soil Microbiology; lesy; Fungi; půda